Wearing face masks impairs dyadic micro-activities in nonverbal social encounter: A mixed-methods first-person study on the sense of I and Thou - Wagemann, Johannes; Tewes, Christian; Raggatz, Jonas (Frontiers in Psychology, 2022)
The COVID-19 pandemic has manifold negative consequences for people around the world, of which the psychosocial ones have been rather underrepresented in the public eye. Regarding social distancing measures, there is already some experimental work demonstrating that the use of face masks has detrimental effects on various aspects of social cognition such as emotion reading, face identification, and perceived closeness of persons. However, while these findings provide important clues, they do not shed light on what people experience when interacting in real life in a masked society. Therefore, in critical distance to cognitivist accounts and taking Direct Social Perception (DSP) approaches seriously, we developed a first-person experimental design and conducted a study with thirty-four participants in a dyadic setting with two conditions (without vs. with face mask). Data were analyzed with mixed methods including in-depth qualitative coding at three levels, code relations analyses, and various statistical tests. Results yielded significant differences across conditions at all qualitative levels, comprising, for example, expressive behavior, and, in particular, significant decreases of content-independent, complimentary mental micro-activities. In the context of DSP, we argue in the paper that these activities suggest the constitution of a quasi-sensory modality – conceived as I-Thou sense – that oscillates between strongly and weakly embodied mental activities, as the analyses show. In sum, this study suggests that mask-wearing impairs both functional directions of mental activity in relation to more or less embodied experience and thus intervenes deeply in fundamental processes of social perception and interaction.